2021
DOI: 10.1021/acs.est.0c08752
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role of the Fungal Community in Variations of the Antibiotic Resistome in the Soil Collembolan Gut Microbiome

Abstract: Fertilization is known to affect antibiotic-resistance gene (ARG) patterns in the soil, even in the gut of soil fauna. Here, we conducted a microcosm experiment to investigate differences of effects of different fertilizers on collembolan gut ARG profiles and to further explore the microecological mechanisms that cause the differences. Although fertilization increased the abundance of ARGs, compared with the conventional manure, the application of antibiotic-reduced manure and vermicompost all curbed the enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…In particular, through relevant research of 147 genera of fungi, it was found that 14 genera of fungi were detected for the first time in the coastal environment, among which the abundance of 2 genera— Laetisaria [ 26 ] and Spirosphaera [ 27 ]—ranked in the top 10 of all fungi. The remaining 12 fungal genera were as follows: Gibellulopsis [ 28 ], Monacrosporium [ 29 ], Spegazzinia [ 30 ], Rhizopycnis [ 31 ], Dokmaia [ 32 ], Vermispora [ 33 ], Hirsutella [ 34 ], Erythricium [ 35 ], Limonomyces [ 36 ], Entorrhiza [ 37 ], Dinemasporium [ 38 ], and Villosiclava [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, through relevant research of 147 genera of fungi, it was found that 14 genera of fungi were detected for the first time in the coastal environment, among which the abundance of 2 genera— Laetisaria [ 26 ] and Spirosphaera [ 27 ]—ranked in the top 10 of all fungi. The remaining 12 fungal genera were as follows: Gibellulopsis [ 28 ], Monacrosporium [ 29 ], Spegazzinia [ 30 ], Rhizopycnis [ 31 ], Dokmaia [ 32 ], Vermispora [ 33 ], Hirsutella [ 34 ], Erythricium [ 35 ], Limonomyces [ 36 ], Entorrhiza [ 37 ], Dinemasporium [ 38 ], and Villosiclava [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…59,60 For example, Talaromyces and Penicillium, belonging to Ascomycota, can produce a variety of secondary metabolites with antibacterial activities, thus likely playing a role in shaping the antibiotic resistome. 61,62…”
Section: Sludge Application Increases the Risks Of Xylem Resistomesmentioning
confidence: 99%
“…Soil animals are an important component of soil ecosystems, performing many important ecological functions . Soil animals have a high species diversity and are distributed in almost all soils. , Since soil animals tend to ingest organic matter, , the application of organic fertilizers is expected to enrich ARGs in the soil animal microbiome. , Further, diverse antibacterial substances and antibiotic gene clusters have been detected in the intestinal tract of soil animals, suggesting that soil animals may possess abundant intrinsic resistance. Thus, the ARGs of soil animals may play an important role as a resistome in soil ecosystems.…”
Section: Introductionmentioning
confidence: 99%